2008
DOI: 10.1161/strokeaha.107.503458
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Pretreatment With the Angiotensin II Type 1 Receptor Blocker, Valsartan, Prevents Ischemic Brain Damage Through an Increase in Capillary Density

Abstract: Background and Purpose-We investigated the effect of temporary treatment with a nonhypotensive dose of valsartan on ischemic brain damage in C57BL/6 mice. Methods-We separated the mice into 3 groups of valsartan treatment before middle cerebral artery (MCA) occlusion: (1) for 4 weeks: Val (2W, 2W); (2) for 2 weeks followed by its cessation for 2 weeks: Val (2W, -); and (3) no treatment for 4 weeks: Val (-, -). Results-Ischemic volume, DNA damage, superoxide production, and mRNA levels of monocyte chemoattracta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
2
28
2
Order By: Relevance
“…Another important downstream effect of endothelial nitric oxide is angiogenesis, and brain capillary density determines stroke outcome in mice. 28 Here, ivabradine significantly increased capillary density both in naive and in stressed mice, consistent with the importance of vascular nitric oxide for the ivabradine effects. In summary, these findings support the concept of heart rate reduction as an intervention to conserve endothelial integrity.…”
Section: Custodis Et Alsupporting
confidence: 78%
See 1 more Smart Citation
“…Another important downstream effect of endothelial nitric oxide is angiogenesis, and brain capillary density determines stroke outcome in mice. 28 Here, ivabradine significantly increased capillary density both in naive and in stressed mice, consistent with the importance of vascular nitric oxide for the ivabradine effects. In summary, these findings support the concept of heart rate reduction as an intervention to conserve endothelial integrity.…”
Section: Custodis Et Alsupporting
confidence: 78%
“…28 Chronic stress did not affect density of CD31-positive cells in the brain. Heart rate reduction with ivabradine increased the number of CD31-expressing cells in naive mice from 4503Ϯ501/mm 2 to 6794Ϯ485/mm 2 (PϽ0.05).…”
Section: Brain Capillary Densitymentioning
confidence: 86%
“…31,32 Moreover, we have reported previously that capillary density in the brain was increased by treatment with an ARB. 33 These results suggest that these beneficial effects on cerebral vessels by blockade of the AT 1 receptor could contribute to suppression of the decrease in CBF.…”
Section: Discussionmentioning
confidence: 90%
“…31 Furthermore, our previous report demonstrated that treatment with an ARB, valsartan, increased capillary density in the brain. 32 Therefore, we speculated that treatment with an even lower dose of telmisartan would increase CBF, with PPAR-␥ activation as well as AT 1 receptor blockade.…”
Section: Discussionmentioning
confidence: 99%